Review of Popularization A Historical and Cultural Analysis of 50 Years of Dutch Political Television Journalism by R. Van Santen. Amsterdam, the Netherlands: Almanakker, Oosterhout, 2012, 196 pages - Florina Crețu (Romanian Journal of Communications and Public Relations, 2023)
In the last couple of decades various scholars have signaled the occurrence and development of important processes in political communication. If some have broadly coined these transformations as “Americanization” (Negrine & Papathanassopoulos, 1996; Scammel, 1998), “professionalization” (Blumler & Kavanaugh, 1999; Strömbäck, 2008; Stamper & Brants, 2011), “tabloidization” (Barnett, 1998; Connell, 1998; Klein, 1996) or “infotainment”, (Street, 2000; 2001), others have associated them with terms such as “video malaise” (Robinson, 1976) or “spectatorship democracy” (De Beus, 2011). According to these views, political journalism nowadays has stepped into a new era, in which the coverage of political events and television programming itself are heading towards an entertainment logic. Rosa Van Santen’s work addresses all of these issues and represents a very valuable contribution to assessing these hypotheses.